Why do we quote? the culture and history of quotation - Finnegan, Ruth H.; Open Book Publishers (Open Book Publishers, 2011)
"Quoting is all around us. But do we really know what it means? How do people actually quote today, and how did our present systems come about? This book brings together a down-to-earth account of contemporary quoting with an examination of the comparative and historical background that lies behind it and the characteristic way that quoting links past and present, the far and the near. Drawing from anthropology, cultural history, folklore, cultural studies, sociolinguistics, literary studies and the ethnography of speaking, Ruth Finnegan's fascinating study sets our present conventions into cross-cultural and historical perspective. She traces the curious history of quotation marks, examines the long tradition of quotation collections with their remarkable recycling across the centuries, and explores the uses of quotation in literary, visual and oral traditions. The book tracks the changing definitions and control of quoting over the millennia and in doing so throws new light on ideas such as 'imitation', 'allusion', 'authorship', 'originality' and 'plagiarism'."--Publisher's website.
Preface -- I. Setting the present scene -- 1. Prelude: a dip in quoting's ocean -- 2. Tastes of the present: the here and now of quoting -- 3. Putting others' words on stage: arts and ambiguities of today's quoting -- II. Beyond the here and now -- 4. Quotation marks present, past, and future -- 5. Harvesting others' words: the long tradition of quotation collections -- 6. Quotation in sight and sound -- 7. Arts and rites of quoting -- 8. Controlling quotation: the regulation of others' words and voices -- III. Distance and presence -- 9. What is quotation and why do we do it? -- Appendix 1: Quoting the academics -- Appendix 2. List of the Mass Observation writers -- References -- Index.
Available through Open Book Publishers.
Includes bibliographical references (pages 299 -319) and index.
Mode of access: World Wide Web.
Keywords: Quotation -- Social aspects; Quotation; Quotations -- History